Drivers of hibernation in the brown bear. Issue 1 (December 2016) - Evans, A.; Singh, N.; Friebe, A.; Arnemo, J.; Laske, T.; Fröbert, O.; Swenson, J.; Blanc, S.
Abstract Background Hibernation has been a key area of research for several decades, essentially in small mammals in the laboratory, yet we know very little about what triggers or ends it in the wild. Do climatic factors, an internal biological clock, or physiological processes dominate? Using state-of-the-art tracking and monitoring technology on fourteen free-ranging brown bears over three winters, we recorded movement, heart rate (HR), heart rate variability (HRV), body temperature (Tb ), physical activity, ambient temperature (TA ), and snow depth to identify the drivers of the start and end of hibernation. We used behavioral change point analyses to estimate the start and end of hibernation and convergent cross mapping to identify the causal interactions between the ecological and physiological variables over time. Results To our knowledge, we have built the first chronology of both ecological and physiological events from before the start to the end of hibernation in the field. Activity, HR, and Tb started to drop slowly several weeks before den entry. Bears entered the den when snow arrived and when ambient temperature reached 0 °C. HRV, taken as a proxy of sympathetic nervous system activity, dropped dramatically once the bear entered the den. This indirectly suggests that denning is tightly coupled to metabolic suppression. During arousal, the unexpected early rise in Tb (two months before den exit) was driven by TA, but was independent of HRV. The difference between Tb and TA decreased gradually suggesting that bears were not thermoconforming. HRV increased only three weeks before exit, indicating that late activation of the sympathetic nervous system likely finalized restoration of euthermic metabolism. Interestingly, it was not until TA reached the presumed lower critical temperature, likely indicating that the bears were seeking thermoneutrality, that they exited the den. Conclusions We conclude that brown bear hibernation was initiated primarily by environmental cues, but terminated by physiological cues.